- Pemanfaatan Solar Energy Kit sebagai Media Edukasi Energi Terbarukan di Lingkungan Sekolah: - - Muh Ilham Fahmiy Fahmiy; Dhanang Suryo Prayogo; Dina Novera Serfandi; Alfiana Nur Hidayati (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2026)
The limited availability of interactive teaching aids hinders students from understanding renewable energy concepts in depth. This community service study aimed to improve energy literacy among 60 high school students (30 per school) at Almaarif Islamic High School Singosari and Diponegoro Islamic High School Wagir using the Solar Energy Kit as an educational medium. A participatory, learning-by-doing method was employed, encompassing interactive lectures, tool demonstrations, and hands-on assembly practice in small groups. Students assembled photovoltaic systems and measured electrical output under varying sunlight conditions using a built-in multimeter. Pre- and post-test results showed an average knowledge gain of 40.6%, and questionnaire responses indicated a significant increase in students' interest in eco-friendly technology and environmental awareness. The Solar Energy Kit is an effective and practical teaching medium that is recommended for integration into the school science curriculum.